“12 пьес на народные темы” Комитаса: опыт методического анализа - Софья Казарян (ՀՀ ԳԱԱ հրատ.)
Այս հոդվածում մեր ուշադրության կենտրոնում է Կոմիտասի «12 պիես ժողովրդական թեմաներով» մանկական դաշնամուրային շարքը, որն առանձնանումէ թե՝ իր պատմական և թե՝ գեղարվեստական նշանակությամբ: Այն առաջիններից է ազգային երաժշտական ռեպերտուարում, որը հիմնված է ֆոլկլորի վրա և հատուկ նախատեսված է մանկական դաշնամուրային նախնական ուսուցման համար: This article elaborates on “12 pieces on folk themes”, piano works for children by Komitas. They are of distinction for both their historical and artistic significance. They are among the first piano pieces in the Armenian national music repertoire, constructed on folk music and especially designed for children just beginning to learn the piano.
Keywords: Music; Folk, National and Ethnic Music